(untitled) - Asian Development Bank (Philippines, 2006)
This book includes state of the agriculture sector, strategic challenges and the vision, implementation of the agriculture and rural development strategy.
Keywords: Rural development,Phát triển nông thôn; Indonesia,Indonesia